2020
DOI: 10.3390/plants9121778
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Patterns of Bermuda Grass along Latitudinal Gradients at Different Temperatures in Southeastern China

Abstract: Cynodon dactylon (L.) Pers. (common Bermuda grass) has a limited capacity to grow at low temperatures, which limits its geographical range. Exploring its evolutionary relationship across different environmental gradients is necessary to understand the effects of temperature change on the genetics of common Bermuda grass. In this study, high-throughput transcriptome sequencing was performed on 137 samples of C. dactylon from 16 latitudinal gradients to explore the differential molecular markers and analyze gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Plants that do not demonstrate thermal acclimation produce membrane fatty acid profiles with greater saturated: unsaturated fatty acid ratios, whereas plants that show thermal acclimation produce membrane fatty acid profiles with greater unsaturated: saturated fatty acid profiles. Greater concentrations of C16:1n7, C18:1n9t, C18:2n6, C18:3n3, and C20:5n3 in Marianna corroborated with Fontanier et al (2020), Hu et al (2017), Zhang et al (2020), and Zamanian et al, 2021 that also observed greater unsaturated fatty acid concentrations in bermudagrass grown under cold stress conditions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Plants that do not demonstrate thermal acclimation produce membrane fatty acid profiles with greater saturated: unsaturated fatty acid ratios, whereas plants that show thermal acclimation produce membrane fatty acid profiles with greater unsaturated: saturated fatty acid profiles. Greater concentrations of C16:1n7, C18:1n9t, C18:2n6, C18:3n3, and C20:5n3 in Marianna corroborated with Fontanier et al (2020), Hu et al (2017), Zhang et al (2020), and Zamanian et al, 2021 that also observed greater unsaturated fatty acid concentrations in bermudagrass grown under cold stress conditions.…”
Section: Discussionsupporting
confidence: 72%
“…is a productive warm‐season perennial grass cultivated in more than 9 million hectares in the US (Ximenes et al, 2008). The bermudagrass adaptation zone ranges from latitude 45° N to 45° S with superior herbage accumulation (HA) and nutritive value during the warm season (Zhang et al, 2020). Vendramini et al (2021) compared different cultivars of bermudagrass in Ona‐FL and concluded that Mislevy had similar total HA to Jiggs (~14,500 kg DM ha −1 ) and greater HA than Tifton 44 (13,100 kg DM ha −1 ), Tifton 85 (13,800 kg DM ha −1 ), and Coastal (8400 kg DM ha −1 ) during the experimental period from March to October.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive divergence associated with thermal plasticity has been observed in natural populations of Plantago lanceolata [ 63 ] and Cynodon dactylon [ 64 ] along large-scale latitudinal gradients. However, a study finding annual thermal plasticity associated with population adaptive divergence along small-scale latitudinal gradients, to our knowledge, has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have investigated the morphological diversity of a vast collection of bermudagrass. The collection is enriched by China, particularly subtropical and mesothermal zones, representing a wealth of local genetic resources that might be exploited in future conservation and breeding studies [ 3 , 23 ]. However, it was challenging and limited to study the regulatory mechanisms of bermudagrass plant type regulation without the genome information before the disclosure of the African bermudagrass genome sequence in August 2021 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%